A critical consideration of the exclusion of corporate criminal liability for the atrocity crimes under the Rome Statute of the International Criminal Court - Masake, Pilisano Harris (Stellenbosch : Stellenbosch University, 2019)
Thesis (LLD)--Stellenbosch University, 2019.